2015
DOI: 10.7863/ultra.14.12032
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Differences in the Sacral Hiatus During Caudal Epidural Injection Using Ultrasound Guidance

Abstract: audal epidural steroid injection can be helpful for treatment of symptomatic low back pain caused by lumbar disk herniation or spinal canal stenosis. [1][2][3][4][5][6] The caudal epidural steroid injection technique involves injection of a steroid into the epidural space via the sacral hiatus and is often preferred by nonanesthetists because it carries a lower risk of inadvertent thecal sac puncture or intrathecal injection. 7,8 The sacral hiatus is a triangular aperture located at the caudal end of the sacru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 23 publications
1
10
1
2
Order By: Relevance
“…The mean anterior-posterior (AP) diameter of sacral hiatus at its apex ranges from 4.6 ± 2 mm to 6.1 ± 2.1 mm [6, 7, 914] and decreased with age [14]. In clinical settings, an AP diameter of sacral hiatus at the apex of less than 3.7 mm was associated with difficulty in inserting a needle into the caudal epidural space by blind technique [13].…”
Section: Anatomymentioning
confidence: 99%
“…The mean anterior-posterior (AP) diameter of sacral hiatus at its apex ranges from 4.6 ± 2 mm to 6.1 ± 2.1 mm [6, 7, 914] and decreased with age [14]. In clinical settings, an AP diameter of sacral hiatus at the apex of less than 3.7 mm was associated with difficulty in inserting a needle into the caudal epidural space by blind technique [13].…”
Section: Anatomymentioning
confidence: 99%
“…Kao and Lin (2017) reviewed values for the mean depth of the sacral hiatus (i.e., the anteroposterior diameter of the midsagittal vertebral canal) at the level of its apex. This was reported to be 6.0 mm by Sekiguchi et al (2004), 4.5 mm by Crighton et al (1997), or 4.5 mm by Senoglu et al (2005), and this value decreases with age (Park, Kwon, & Cho, 2015). However, the hiatus depth may be as little as 2 mm or less in 1–6.3% of cases (Senoglu et al, 2005).…”
Section: Discussionmentioning
confidence: 93%
“…The length of the sacral hiatus has been linked to complications in procedures involving entry into the sacral canal 24,25 . It has been found that the longer length of the sacral hiatus is directly related to increase in the incidence of dural puncture.…”
Section: Morphometric Differencesmentioning
confidence: 99%